2021
DOI: 10.3390/ma15010136
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Processing Parameters on the Porosity and Mechanical Behavior of Titanium Samples with Bimodal Microstructure Produced via Hot Pressing

Abstract: Commercially pure (c.p.) titanium grade IV with a bimodal microstructure is a promising material for biomedical implants. The influence of the processing parameters on the physical, microstructural, and mechanical properties was investigated. The bimodal microstructure was achieved from the blends of powder particles with different sizes, while the porous structure was obtained using the space-holder technique (50 vol.% of ammonium bicarbonate). Mechanically milled powders (10 and 20 h) were mixed in 50 wt.% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 76 publications
1
10
1
Order By: Relevance
“…The characteristics of suspensions, emulsions, and mixtures often used in powder-based manufacturing depend largely on powder materials size, shape and distribution of powder materials. These factors control the porosity and mechanical properties of sintered 13 and additively manufactured samples 14 , improves flowability and wettability of yield stress fluids 15 , and influence thermal and electrical conductivity 16 . Therefore, characterizing the particle size distribution before and during manufacturing becomes important at advanced production and scientific facilities 17 – 19 .…”
Section: Introductionmentioning
confidence: 99%
“…The characteristics of suspensions, emulsions, and mixtures often used in powder-based manufacturing depend largely on powder materials size, shape and distribution of powder materials. These factors control the porosity and mechanical properties of sintered 13 and additively manufactured samples 14 , improves flowability and wettability of yield stress fluids 15 , and influence thermal and electrical conductivity 16 . Therefore, characterizing the particle size distribution before and during manufacturing becomes important at advanced production and scientific facilities 17 – 19 .…”
Section: Introductionmentioning
confidence: 99%
“…Previous research has shown that porosity percentages greater than 45 % are necessary to attain an elastic modulus comparable to that of human bone [11]. These porosity levels lead to a drastic reduction in the mechanical resistance, compromising implant reliability [12]. Nonetheless, there exist three main reinforcement strategies that can counteract the decrease in mechanical strength stemming from porosity: (i) composition design, (ii) processing technique, and (iii) thermal treatment [13].…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of materials can be employed as space-holder particles, from ceramic particles, soluble salts, polymers, to metallic spheres [20]. For biomedical applications, the commonly materials for space-holders are NH 4 HCO 3 [5,12,[21][22][23], NaCl [20,21,[23][24][25], starch [26,27], Mg [1,28,29], PMMA [30,31], saccharose crystals [27,32], PVA [33], and carbamide [19,34,35], due to its easy removal ability by decomposition at relatively low temperatures or by means of dissolution process, generally in water [9,12]. According to the literature, the use of NaCl as a spacer has advantages, such as low cost, rapid dissolution in water, reduced metal etching during dissolution, as well as much lower toxicity due to residual content [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations